The Effectiveness of Leaflet and Video Educational Media Through Whatsapp toward the Knowledge of Type 2 DM Patients - I Made Rai Mahardika; Ni Made Ayu Sukma Widyandari (Babali Nursing Research, 2023)
Diabetes Mellitus (DM) is a metabolic disease with characteristics of hyperglycemia that occurs due to abnormalities in the secretion of insulin, the action of insulin or both. Diabetes is known as a silent killer because when it is known that complications have occurred. Complications can be prevented through a good understanding and knowledge of diabetes. Knowledge of DM patients can be improved through the provision of Education. There are various ways of providing education such as the type of media used and how education is given. The purpose of the study was to determine the effectiveness of leaflet education media and video education media through Whatsapp application to the knowledge of Type 2 DM patients. The research design used is quasi experimental design using pre-test and post-test with control group design. The sample consisted of 112 people divided into two groups, 56 people in the control group (leaflet media) and 56 people in the intervention group (video media). Sampling technique by purposive sampling. The results showed that health education provided with leaflets and video media via Whatsapp had an effect on improving the knowledge of Type 2 DM patients (p-value 0.000). The results of Independent T-Test showed the mean value on the leaflet media 12.10 and the mean on the video media 13.28 with a p-value of 0.019. Conclusion: the provision of health education using video media via Whatsapp is more effective in improving knowledge in Type 2 DM patients than using leaflet media via Whatsapp.